Working with patients’ treatment expectations – what we can learn from homeopathy - Wilhelm, Marcel; Hermann, Christiane; Rief, Winfried; Schedlowski, Manfred; Bingel, Ulrike; Winkler, Alexander (Frontiers in Psychology, 2024)
The usual homeopathic remedy, “globules”, does not contain any pharmacologically active ingredient. However, many patients and practitioners report beneficial effects of homeopathic treatment on various health outcomes. Experimental and clinical research of the last two decades analyzing the underlying mechanisms of the placebo effect could explain this phenomenon, with patients’ treatment expectations as the predominant mechanism. Treatment expectations can be optimized through various factors, such as prior information, communication, and treatment context. This narrative review analyses how homeopathy successfully utilizes these factors. Subsequently, it is discussed what evidence-based medicine could learn from homeopathic practice to optimize treatment expectations (e.g., using an empathic, patient-centered communication style, deliberately selecting objects in practice rooms, or using clear treatment rituals and salient contextual stimuli) and thereby treatment effectiveness. Homeopathic remedy does not work beyond the placebo effect but is recommended or prescribed as an active treatment by those who believe in it. Thus, practitioners need to understand the manner in which homeopathy (as an example of inert treatment) works and are advised to reintegrate its underlying effective placebo mechanisms into evidence-based medicine. This promises to increase treatment efficacy, tolerability, satisfaction, and compliance with evidence-based treatments, and addresses the desires patients are trying to satisfy in homeopathy in an ethical, fully informed way that is grounded in evidence-based medicine.